Ring of progress: Examining the impact of the intensity of mobile phone use on female labor force participation in India - Cledwyn Fernández; Havishaye Puri (Asian Development Bank Institute (ADBI), 2024)
In this paper, we study the causal impact of the intensity of mobile phone use on female labor force participation in India. Using data from a large representative household survey, we employ an instrumental variable approach to estimate this causal impact. We decompose the intensity of mobile phone use into two channels, namely digital access (sharing a mobile phone) and digital inclusion (exclusively using a mobile phone). We find that while neither digital access nor inclusion has any significant impact on female labor force participation in India, the effect varies across different heterogeneous groups. The digital access effect is positive and significant for females residing in rural India, those with a basic level of education, and those belonging to the lower household consumption quartiles. Conversely, the digital inclusion effect is significant for females residing in urban India, those with higher levels of education, those residing in higher household consumption quartiles, and those belonging to the 15-24 years age group.
Keywords: J21; O30; P25; 330; digital; female labor force participation; rural; urban